Effect of flipped classroom on geometry performance among senior secondary school students in Zaria, Kaduna State, Nigeria - Balarabe, Bashir; Yahaya, Ibrahim El-Ladan; Danlami, Kazaik Benjamin (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2024)
This study aimed to investigate the effect of flipped classrooms on performance in geometry among Senior Secondary school students in Zaria, Kaduna state. The study employed quasi- quasi-experimental research design. The study was guided by two research questions and two null hypotheses. The targeted population of the study was all SSII students in 20 senior public secondary schools in Zaria. Two schools were randomly selected using a simple random sampling technique from among the public secondary schools in Zaria. A sample size consisting of 157 students; 72 students (42 male and 30 female) were assigned to the experimental group and 85 students (44 male and 41 female) were assigned to the control group. The students' average age was 13 years. The experimental group was taught using a flipped classroom and the Control Group was taught using the Conventional (Lecture) method. The Geometry Performance Test (GPT) which consists of 20 multiple-choice questions was used as an instrument for data collection for the study. GPT was subjected to both face and content validity by 3 experts in mathematics education. The GPT was pilot-rested and a reliability coefficient of 0.82 was obtained using Pearson's Product Moment Correlation coefficient. The research questions were answered using descriptive statistics of mean and standard deviation and the null hypotheses were tested at α = 0.05 the level of significance using Analysis of covariance (ANCOVA). The results showed a significant difference in the mean performance score between the experimental group (mean = 67.96, SD = 10.76) and the control group (mean = 36.61, SD = 7.72), F (2, 154) = 473.097, was obtained with a p-value of 0.000. The study also found no significant difference in the mean performance score between male (mean = 68.14, SD = 12.15) and female (mean = 67.70, SD = 8.62) students in the experimental group, F (2, 69) = 0.059, p = 0.982. Based on the findings it was recommended among others that professional bodies such as MAN, STAN, etc. should imbibe Flipped Classroom in the theme of workshops, seminars, and conferences to train mathematics teachers on the use of innovative strategies like the flipped classroom